Should Australia Ban the Use of Genetic Test Results in Life Insurance? - Tiller, Jane; Otlowski, Margaret; Lacaze, Paul (Frontiers in Public Health, 2017)
Under current Australian regulation, life insurance companies can require applicants to disclose all genetic test results, including results from research or direct-to-consumer tests. Life insurers can then use this genetic information in underwriting and policy decisions for mutually rated products, including life, permanent disability, and total income protection insurance. Over the past decade, many countries have implemented moratoria or legislative bans on the use of genetic information by life insurers. The Australian government, by contrast, has not reviewed regulation since 2005 when it failed to ensure implementation of recommendations made by the Australian Law Reform Commission. In that time, the Australian life insurance industry has been left to self-regulate its use of genetic information. As a result, insurance fears in Australia now are leading to deterred uptake of genetic testing by at-risk individuals and deterred participation in medical research, both of which have been documented. As the potential for genomic medicine grows, public trust and engagement are critical for successful implementation. Concerns around life insurance may become a barrier to the development of genomic health care, research, and public health initiatives in Australia, and the issue should be publicly addressed. We argue a moratorium on the use of genetic information by life insurers should be enacted while appropriate longer term policy is determined and implemented.